Power challenges may end the multicore era - Esmaeilzadeh, H.; Blem, Emily R.; St. Amant, Renee; Sankaralingam, Karthikeyan; Burger, Doug (Commun. ACM, 2013)
Starting in 2004, the microprocessor industry has shifted to multicore scaling—increasing the number of cores per die each generation—as its principal strategy for continuing performance growth. Many in the research community believe that this exponential core scaling will continue into the hundreds or thousands of cores per chip, auguring a parallelism revolution in hardware or software. However, while transistor count increases continue at traditional Moore's Law rates, the per-transistor speed and energy efficiency improvements have slowed dramatically. Under these conditions, more cores are only possible if the cores are slower, simpler, or less utilized with each additional technology generation. This paper brings together transistor technology, processor core, and application models to understand whether multicore scaling can sustain the historical exponential performance growth in this energy-limited era. As the number of cores increases, power constraints may prevent powering of all cores at their full speed, requiring a fraction of the cores to be powered off at all times. According to our models, the fraction of these chips that is "dark" may be as much as 50% within three process generations. The low utility of this "dark silicon" may prevent both scaling to higher core counts and ultimately the economic viability of continued silicon scaling. Our results show that core count scaling provides much less performance gain than conventional wisdom suggests. Under (highly) optimistic scaling assumptions—for parallel workloads—multicore scaling provides a 7.9× (23% per year) over ten years. Under more conservative (realistic) assumptions, multicore scaling provides a total performance gain of 3.7× (14% per year) over ten years, and obviously less when sufficiently parallel workloads are unavailable. Without a breakthrough in process technology or microarchitecture, other directions are needed to continue the historical rate of performance improvement.